Prevalencia de anomalías dentarias de tamaño y forma, en pacientes pediátricos de 6 a 17 años de la ciudad de Huánuco, 2019-2022 - Palacios León, Claudia (2023)
Objective: To determine the prevalence of dental anomalies of size and shape in patients aged 6 to 17 years, treated in Huánuco from 2019 to 2022. Methodology: The study was descriptive, retrospective cross-sectional with a sample of 362 Panoramic radiographs of patients 6 to 17 years of age. I make detailed observations for each observation sheet, the patient's age, sex, dental shape and size alterations, the type of dentition presented, the affected quadrant and the type of dental piece. Results: A higher prevalence of dental anomaly of shape was found with 85.10% (308) and of size with 14.9% (54). In relation to the quadrant, the tooth with rhizomycorrhexis presented the highest prevalence with 18.5% (10) in quadrant II while macrodontia presented 13.0% (7) in quadrant I and II, while the shape alteration of the shovel tooth presented the highest prevalence in quadrant II with 24.5% (76). Conclusion: There is a higher prevalence of shape anomalies as opposed to size anomalies that were less prevalent in the research work, being the female sex and the age group 11 to 17 years the most prevalent.